Role of entrepreneurial universities in Financing innovation and sustainable development - Panda, Hemand K. (University News)
Most university are operating in the public sector and rationally they are not suited for an entrepreneurial role (Kirby, 2006). However, over the past two decades, the world over, universities have been facing new challenges and rapid changes like the increase pace of technological progress, negative demographic shifts, decreasing public funding, new skills, required in the marketplace, and fierce competition for attracting students and research funds. - Reproduced